Manajemen Komunikasi Stigma Terhadap Perempuan Menikah Muda di Lombok Timur, Nusa Tenggara Barat - Islami, Aulia Dina; Hakim, Lukman (LPPM Institut Pendidikan Nusantara Global, 2025)
Early marriage remains a significant social issue in Indonesia, especially in regions such as East Lombok where cultural norms and economic conditions reinforce the practice. Women who marry under the age of 20 are often subjected to multiple forms of social stigma, including physical stereotypes, moral judgments, and social exclusion. This study aims to explore how these young women manage the stigma they face through interpersonal communication strategies. A qualitative approach with a multiple-case study design was employed. Data were collected through in-depth interviews with five early-married women residing in East Lombok. The analysis utilized Meisenbach’s (2010) Stigma Management Communication Theory to identify the types of stigma experienced and the communicative strategies adopted. The findings reveal that the participants encountered three main types of stigma: physical (e.g., being perceived as too young), moral (e.g., viewed as irresponsible), and social (e.g., exclusion from social gatherings). In response, the women employed strategies such as acceptance, avoidance, emotional minimization, and affirmation. These responses were shaped by contextual factors, including the nature of their relationship with the stigmatizer. These communication strategies helped the women maintain psychological resilience and navigate their social environments while preserving self-confidence and agency. This study contributes to the fields of interpersonal communication, gender studies, and stigma management by demonstrating how young women in conservative cultural settings resist negative labeling through context-sensitive communication. The findings underscore the need for culturally grounded support systems to empower early-married women and reduce harmful societal stigmas.